Growth and production of ornamental sunflower irrigated with dilutions of treated domestic sewage - Karoline Santos Gonçalves; Gustavo Araújo Bispo; Samir de Sousa Bandeira; Hans Raj Gheyi; Vital Pedro da Silva Paz (Bioscience Journal, 2020)
The water and nutritional potential of wastewater has been frequently exploited as an alternative water source for the irrigation of crops, especially in regions affected by the scarcity of water resources. Thus, this study aimed to evaluate growth and production of ornamental sunflower (Helianthus annuus L.) cv. Anão de Jardim irrigated with different dilutions of treated domestic sewage in public-supply water. The experiment was conducted in completely randomized design with five treatments and four replicates, in a greenhouse, in the Experimental Area of the Agricultural Engineering Graduate Program of the Federal University of Recôncavo of Bahia, located in the municipality of Cruz das Almas - BA, Brazil. Treatments started seven days after transplanting of the seedlings and consisted of five dilutions of treated domestic sewage (TDS) in public-supply water (PSW) (100% PSW – control; 25% TDS + 75% PSW; 50% TDS + 50% PSW; 75% TDS + 25% PSW and 100% TDS). In the control treatment, plants were fertilized with 100% of the mineral fertilization recommendation, whereas plants in treatments with effluent received 50% of the nitrogen (N) and potassium (K) recommendation. Biometric (plant height, stem diameter, number of leaves, shoot fresh and dry matter and leaf area) and production (capitulum internal and external diameter, capitulum fresh and dry matter, beginning of flowering and full capitulum opening) indicators evaluated at harvest demonstrated that ornamental sunflower plants irrigated with 100% TDS showed similar performance to those irrigated with PSW, which makes it possible to infer on the possibility of replacing PSW by TDS in irrigation, along with the 50% reduction in the recommendation of N and K fertilization, with no damage to the growth and production of ornamental sunflower, cv. Anão de Jardim, thus leading to the saving of good-quality water and fertilizers.